Measuring consumers' dominant value perceptions to determine their purchase intention of luxury fashion consumption - Tong (Tripp) Liu; Carolina Quintero Rodriguez; Wen-Chieh (Melody) Huang (Cogent Business & Management, 2023)
This research aims to determine the Chinese millennials' dominant value perception on their purchase intention of luxury fashion goods. A survey was used to analyse the importance of luxury values such as quality, uniqueness, self-expression, prestige, and brand image when purchasing luxury fashion handbags. Analytical hierarchy process (AHP) was performed to measure the priority of the values. The results indicate that self-expression (e.g. of self-image and aesthetic beauty) is the most dominant value for Chinese millennial participants when purchasing luxury fashion handbags, whereas the prestige value (i.e. the conspicuous presentation of a social identity) has less influence on their purchase intention. This research provides new insight into consumers' luxury value perceptions, consumers' luxury value priorities, and the influence of luxury values on consumers' purchase intention toward a luxury good. This study contributes to luxury fashion businesses and product developers a better understanding of the Chinese millennial consumers' luxury values, which can contribute to product design development and marketing strategies. This study's results were limited to five luxury values, and further research can draw additional results by evaluating other relevant values.
Keywords: 650; analytic hierarchy process; Chinese millennials; consumer behaviour; consumers' luxury value perceptions; luxury fashion; purchase intention